1994
DOI: 10.1007/bf00371568
|View full text |Cite
|
Sign up to set email alerts
|

Lichen sclerosus et atrophicus. A histological, immunohistochemical and electron microscopic study

Abstract: We studied three cases of genital lichen sclerosus et atrophicus (LSA) using histological, immunohistochemical and ultrastructural techniques to elucidate the characteristics of the collagen fibres, the elastic fibres and the interfilamentous matrix in the upper dermal homogeneous zone. In the early stages of LSA, the homogeneous zone caused elaunin fibres to push downwards and partially disappear, the collagen fibres were presumably phagocytosed by fibroblasts, and there were peculiar cells containing numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
4
27
1
2
Order By: Relevance
“…27 Also, electron microscopic studies confirmed alterations of the basal lamina in lichen sclerosus. [24][25][26] The results of our study differ from the findings in morphea where integrity of all studied BMZ structures was preserved. This would suggest that the pathomechanism of morphea differs from that of LS.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…27 Also, electron microscopic studies confirmed alterations of the basal lamina in lichen sclerosus. [24][25][26] The results of our study differ from the findings in morphea where integrity of all studied BMZ structures was preserved. This would suggest that the pathomechanism of morphea differs from that of LS.…”
Section: Discussioncontrasting
confidence: 85%
“…[12][13][14] A thickened basement membrane is of diagnostic significance in LS. 22,23 At the ultrastuctural level, abnormalities of the BMZ are observed, [24][25][26] consisting of absence of anchoring fibrils, as well as invaginations and reduplications of the basal lamina. 27 Some patients display clinical and histologic features of both morphea and lichen sclerosus.…”
mentioning
confidence: 98%
“…BXO and lichen sclerosis appear similar, with characteristic features including hyperkeratosis with atrophic epidermis along with a homogeneous zone with vacuolar degeneration of the basal layer. In the advanced stages, dermal collagen forms a homogenous band at the dermal-epithelial junction in conjunction with elastin fibres, to produce an amorphous hybrid substance [15]. Deep to this amorphous band, a chronic inflammatory cell infiltration, mainly from T cells, is present [16].…”
Section: Discussionmentioning
confidence: 98%
“…Individual necrotic, predominantly basal, keratinocytes are frequently seen because the inflammatory process causes injury to the basal keratinocytes (colloid or Civatte bodies). Numerous clinical conditions can result in vacuolar alteration of the basal keratinocytes, including: viral exanthems, phototoxic dermatitis, acute radiation dermatitis, erythema dyschromicum perstans, 37 lichen sclerosis et atrophicus, 38 erythema multiforme and Stevens-Johnson syndrome, 39 40 erythema multiforme-like drug eruption (fig 9), and fixed drug eruption. 41 Vacuolar alteration is often present in cutaneous connective tissue disorders such as lupus erythematosus 42 43 (fig 10A-D), and dermatomyositis.…”
Section: Interface Dermatitis With Vacuolar Alterationmentioning
confidence: 99%